Algorithm for blind separation of PCMA based on CHASE decoding - Jian DU; Ke-xian GONG; Hua PENG (Tongxin xuebao)
On the basis of SOVA-PSP, a novel algorithm for blind separation of PCMA signal was presented based on CHASE decoding. The results of soft output of SOVA-PSP were sorted based on reliability in the algorithm, the mixed symbols that had low reliability in the sorted results were reconstructed. Compared the euclidian distance between recon-structed signal and received signal, the wrong results can be corrected. Simulation results show that compared with the SOVA-PSP algorithm, the novel algorithm can improve the gain of about 2 dB.